UNVEILING CLINICAL AND ANGIOGRAPHIC PREDICTORS OF RESTENOSIS FOLLOWING PERCUTANEOUS CORONARY INTERVENTION (PCI) IN LEFT ANTERIOR DESCENDING (LAD) ARTERY LESIONS: INSIGHTS FROM A RETROSPECTIVE COHORT STUDY - DURRANI , T; HUSSAIN , I; ASMA , S; DURRANI , H; KHAN , P; HAIDER , A (Biological and Clinical Sciences Research Journal, 2024)
Restenosis, the re-narrowing of coronary arteries post-stenting, continues to be a significant clinical issue, particularly in Left Anterior Descending (LAD) artery lesions. Despite advances in stent technology, including drug-eluting stents (DES), restenosis remains a significant contributor to adverse cardiovascular events such as myocardial infarction and repeat revascularisation. Understanding the clinical and angiographic factors that predict restenosis is crucial for improving patient outcomes. Objective: This study aims to identify clinical and angiographic predictors of restenosis in patients undergoing Percutaneous Coronary Intervention (PCI) for LAD artery lesions. Methods: A retrospective cohort study was conducted at MTI-Hayatabad Medical Complex from January 1, 2023, to December 31, 2023. A total of 162 patients who underwent PCI for de-novo LAD lesions were included. Data regarding patient demographics, comorbidities, lesion characteristics, and stent types were extracted from hospital records. Angiographic follow-up was performed at 12 months post-PCI to assess restenosis, defined as ≥50% luminal narrowing. Multivariate logistic regression analysis was used to identify independent predictors of restenosis. Results: Among the 162 patients, 15.4% (n=25) developed restenosis within 12 months. Diabetes mellitus (OR: 2.74; 95% CI: 1.21–6.24; p=0.014), lesion length (OR: 1.08 per mm; 95% CI: 1.01–1.15; p=0.025), and stent type (DES vs. BMS; OR: 0.42; 95% CI: 0.18–0.98; p=0.046) were identified as significant predictors. Smoking and hypertension were not found to be statistically significant. Conclusion: Diabetes mellitus, lesion length, and the use of drug-eluting stents are independent predictors of restenosis in LAD artery lesions. These findings underscore the need for tailored stenting strategies and enhanced post-PCI management in high-risk patients to reduce restenosis rates and improve long-term outcomes.